The current state of indexing in library tasks - Fujita, Mariângela Spotti Lopes [UNESP] (2012)
At present the assignment of subject descriptors or indexing the content of books is not always associated to the specific context of each library, resulting in many cases in the retrieval of not appropriate materials. This paper analyzes the main challenges and prospects for the indexing of books, progress in the analysis of materials in library catalogs, reviews the procedures, instruments, rules and behaviors used in the analysis and representation of the contents of books. It also shows the interaction between teaching, research and performance necessary for students to develop skills in analysis, representation and information retrieval, and the principles-perhaps less obvious - of knowledge organization. The study shows that the policies of management information, more quantitative than qualitative, leave in the background intellectual processing content, thus impairing the retrieval of materials through the library catalog. Finally, the proposal contains a number of teaching materials related to the descriptors allocation in library contexts.